(untitled) (Revista Argentina de Cirugía, 2026)
Background: In Argentina, the specialty of general surgery is in crisis, and this alarming situation is associated with the poor working conditions of general surgeons. Objective: The aim of this study is to describe the perception of young surgeons at the end of their training program, in relation to their job prospects, surgical and academic activity. Material and methods: We conducted a cross-sectional study based on a survey responded by young surgeons in Cordoba, Argentina. Results: The survey was responded by 53 young surgeons; 58% were men and median age was 32 years. Seventy-two percent practiced general surgery and 55% worked in the private setting. Thirtyfour percent were members of Asociación de Cirugía de Córdoba and 23% belonged to Asociación Argentina de Cirugía. As for professional experience, 53.1% were junior surgeons and 64% were capable of performing low or medium complexity procedures. Eighty-nine percent considered that young surgeons do not get a job quickly and 96.2% reported that they were not well paid for their practice. When asked about their personal and professional quality of life, 57% expressed frustration and economic uncertainty. Among women surgeons, 73% reported gender inequities and 50% reported sexual harassment in the workplace. Conclusion: Young surgeons perceived they had low level of competencies for high complexity surgical procedures and reported low rate of membership in surgical societies. Most of them feel frustrated due to scarce job opportunities and expressed economic uncertainty. Nowadays, abuse and harassment of women surgeons still prevails and persists